Traditional Chinese State Ritual System of Sacrifice to Mountain and Water Spirits - Jia, Jinhua (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the traditional Chinese ritual system of sacrifice to mountain and water spirits, a significant but largely overlooked sub-field of Chinse religious studies. This system mainly comprised the five sacred peaks, five strongholds, four seas, and four waterways, and was maintained for two thousand years in imperial China. As state ritual, it was constructed of by Confucian ritual culture, but in practice, it gradually interacted and integrated with various religious traditions, such as Daoism, Buddhism, and folk belief, especially in its local manifestation and dissemination. The eighteen great mountains and waters marked geographical and directional borders and territories modelled on the yin-yang and five-phase framework that helped shape Chinese people's cosmographical understanding of the world. Together, they constituted a set of sacred spaces symbolizing the sanctioned political legitimacy of the imperium and functioning as the loca for communication with the divine, as well as the media between religion and its secular context, state ideology and local beliefs, or various ethnic groups. Through the discovery of a rich variety of historical sources, especially stele inscriptions preserved in the sacrificial temples, the contributors of the ten chapters in this volume examine the sacred peaks, strongholds, seas, and waterways respectively. While each of the chapters explores one or more perspectives, together they reveal the rich implications and ramification of the ritual system and present the first comprehensive study of this sub-field.